2021
DOI: 10.1039/d1ra04405b
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency solid-phase microextraction performance of polypyrrole enhanced titania nanoparticles for sensitive determination of polar chlorophenols and triclosan in environmental water samples

Abstract: A PPy/TiO2 nanocomposite coating was fabricated by direct electropolymerization of pyrrole on annealed TiO2 nanoparticles and evaluated as a novel direct immersion solid phase microextraction fiber coating for the extraction of trace pollutants in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Moreover, Azzollini et al [ 106 ] further demonstrated the antifungal properties of 2-nonanone, as their results clearly indicated that microorganisms triggered a chemical defense in response to the presence of other microorganisms. Researchers continue to develop and refine SPME approaches, both with respect to the employed derivatization strategies [ 107 ] and the novel stationary phases used in the fiber coatings, such as graphene oxide [ 108 ] or its modification with polyaniline/polypyrrole [ 109 ] or polypyrrole-enhanced titania nanoparticles [ 110 ], to improve the method's sensitivity, reproducibility, and linearity range.…”
Section: Methodological Considerations In Bacterial Voc Analysismentioning
confidence: 99%
“…Moreover, Azzollini et al [ 106 ] further demonstrated the antifungal properties of 2-nonanone, as their results clearly indicated that microorganisms triggered a chemical defense in response to the presence of other microorganisms. Researchers continue to develop and refine SPME approaches, both with respect to the employed derivatization strategies [ 107 ] and the novel stationary phases used in the fiber coatings, such as graphene oxide [ 108 ] or its modification with polyaniline/polypyrrole [ 109 ] or polypyrrole-enhanced titania nanoparticles [ 110 ], to improve the method's sensitivity, reproducibility, and linearity range.…”
Section: Methodological Considerations In Bacterial Voc Analysismentioning
confidence: 99%
“…Polypyrrole (PPy), as a conductive polymer, has shown great potential in the field of SPME due to its unique electronic structure and adsorption properties (Du et al, 2021;Ma et al, 2021). The adsorption capacity of PPy can be significantly enhanced by introducing dopants (Khan et al, 2021;Pal et al, 2023;Yu et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Hence, monitoring TCS levels in hygienic products is of high importance. 6 At present, there are multiple methods such as chromatography techniques, [7][8][9] spectrophotometry, 10 and electrochemical sensors 11 for TCS detection. However, majority of these techniques require experience in handling, large amounts of reagents, and are time-consuming.…”
Section: Introductionmentioning
confidence: 99%